2020
DOI: 10.21511/im.16(1).2020.06
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and technology transfer networking platforms in modern research universities

Abstract: Innovative development of Ukraine is possible due to the introduction of an effective mechanism for the promotion of commercially attractive scientific ideas and developments, which are produced at universities, into the domestic and international markets. It is extremely difficult for research universities to negotiate the transfer of their developments due to the lack of an extensive technology transfer infrastructure where an information system would be in place to exchange technological requests and propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The analysis results showed that in the creative sphere, preference is given to personal qualities. At the same time, education and skills can also be obtained through short training courses or even online platforms (Novikova et al, 2020). Some respondents noted that insufficient education is not the main barrier to recruitment.…”
Section: Human Resourcesmentioning
confidence: 99%
“…The analysis results showed that in the creative sphere, preference is given to personal qualities. At the same time, education and skills can also be obtained through short training courses or even online platforms (Novikova et al, 2020). Some respondents noted that insufficient education is not the main barrier to recruitment.…”
Section: Human Resourcesmentioning
confidence: 99%
“…In the UK, marketing communications play an important role and, as a rule, every information institution has such a specialized department in its structure or uses the services of external marketing consultants to promote their projects on the market and expand the share of library information services on the global information market. The transfer of technologies in universities based on a network approach is widely described by Novikova et al (2020). Hajdikova and Polanecka (2013) outlined the methods of using marketing technologies in education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The problem of comparing universities arises not only in terms of competition but also in terms of their consolidation and merger, management of these processes from planning to full integration (Sułkowski et al, 2019). Comparison is also necessary for the formation of knowledge and technology transfer networking platforms (Novikova et al, 2020) and can be valuable in developing targeted forms of cooperation between universities and businesses (Rayevnyeva et al, 2018). Scientometric (bibliometric) analysis is one of the most common methods for assessing and comparing universities' scientific productivity, but it only gives a narrow picture of their activities and is often insufficient (Cancino et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%